Evaluasi Sistem Pengendalian Internal atas Persediaan Bahan Baku pada PT Simex Pharmaceutical Indonesia - Marisa Putri Aulia; Ahmad Syarief (Indonesian Accounting Literacy Journal, 2021)
This Final Project research aims to provide an overview and evaluate the application of internal control over raw materials inventory at PT Simex Pharmaceutical Indonesia, a company engaged in manufacturing of pharmaceutical products. The research method used is qualitative method using data analysis tools, namely control matrix. The data collection technique used interviews, observation, documentation and questionnaires distributed to employees who are directly involved with raw materials inventory. Based on the data analysis, it can be concluded that the implementation of the internal control system for raw materials inventory at PT Simex Pharmaceutical Indonesia has adequated and meets the objectives of internal control according the framework of the Committee of Sponsoring Organizations of the Treadway Commission (COSO). Although the internal control system for raw materials inventory has adequated, the shortages should be improved and the implementation is increased to run more effectively.